Improved dielectric performance of barium strontium titanate multilayered capacitor by means of pulsed laser deposition and slow injection sol-gel methods - Balachandran, Ruthramurthy; Ong, Boon Hoong; Wong, Hin Yong; Tan, Kar Ban; Yow, Ho Kwang; Lee, Wai Keat (Carl Hanser Verlag, 2014)
A Pt/BST/NiFe/Cu multilayered capacitor was fabricated incorporating a polycrystalline Ba0.5Sr0.5TiO3 (BST) film deposited using the pulsed laser deposition technique. Qualitative X-ray diffraction analysis confirmed a perovskite structure for the deposited BST dielectric films which were fired at various temperatures. No intermediate phase was discernable with a post-annealing temperature of 750°C and highly crystallized thin film was obtained at a post-annealing temperature of 800°C. The fabricated capacitor with a BST film thickness of 665 nm exhibited respectable electrical performance with a dielectric constant, k of 657 and a dielectric loss, tan δ = 0.0137 at room temperature at an applied frequency of 1 MHz. The recorded charge storage density and leakage current density were 4.6 μC cm-2 and 33 nA cm-2, respectively, with ±5 V bias.